Adult Low-Hypodiploid Acute B-Lymphoblastic Leukemia With IKZF3 Deletion and TP53 Mutation: Comparison With Pediatric Patients. Issue 2 (1st August 2015) - Fang, Min; Becker, Pamela S.; Linenberger, Michael; Eaton, Keith D.; Appelbaum, Frederick R.; Dreyer, ZoAnn; Airewele, Gladstone; Redell, Michele; Lopez-Terrada, Dolores; Patel, Ankita; Rabin, Karen R.; Lu, Xinyan
Abstract: Objectives: Chromosomal ploidy is a major risk stratification tool for acute B-cell lymphoblastic leukemia (B-ALL). Low hypodiploidy and near-haploidy are thought to be confined to pediatric B-ALL and associated with a poor prognosis. Doubling of either a low-hypodiploid or a near-haploid clone results in an apparently high-hyperdiploid karyotype, which is often misclassified for risk. Methods: We studied four patients with B-ALL who had chromosome genomic array testing (CGAT), along with fluorescence in situ hybridization and mutation testing. Results: We identified a unique case of adult B-ALL with masked low hypodiploidy (mLH) by genomic duplication, along with a somatic deletion of the IKZF3 gene and a somatic TP53 mutation. Three cases of pediatric B-ALL with mLH, two with TP53 mutations and one untested, were also identified and compared with the adult patient. Conclusions: CGAT was critical in the genotype clarification of these cases through detection of copy-neutral loss of heterozygosity and should be considered performing for B-ALL with apparent hyperdiploidy for accurate prognostic risk stratification and treatment planning.